Magnetic and dielectric properties of magnesium substituted cobalt ferrite samples synthesized via one step calcination free solution combustion method. Issue 9 (15th June 2017) - Thomas, Nygil; Jithin, P.V.; Sudheesh, V.D.; Sebastian, Varkey
Abstract: Magnesium substituted cobalt ferrite samples were prepared using solution combustion synthesis without any post-heat treatment. Structural characterization confirms the pure spinel phase with high crystallinity. The cation distribution of the samples was calculated using the value of lattice parameter obtained from Rietveld refinement. Hard to soft magnetic transition was observed as magnesium progressively replaces cobalt in spinel phase. Dielectric properties exhibit a behaviour which is similar to what has been reported for spinel ferrite family. This behaviour could be explained by a Maxwell–Wagner interfacial type polarization.